THE COMMUNICATION STRATEGY OF THE NGO SEKOLAH RELAWAN IN THE CROWDFUNDING CAMPAIGN FOR PALESTINE ON THE BAIKITUMUDAH.COM WEBSITE - Hannanda Yusufany; Engga Probi Endri (MediaKom : Jurnal Ilmiah Komunikasi, 2026)
The Development of information technology, particularly the internet and smartphones, has created new opportunities for non-profit organizations, including leveraging crowdfunding platforms to support social initiatives. This study analyzes the communication strategies employed by the NGO Sekolah Relawan in its crowdfunding campaign for Palestine on the website baikutumudah.com. Using a descriptive qualitative approach, data were collected through observation, interviews, and document analysis with purposive sampling techniques. The findings reveal that Sekolah Relawan successfully implemented the concept of effective communication strategies developed by Ronald Smith, encompassing situational analysis, organizational analysis, public analysis, setting objectives and goals, formulating strategic actions in response, utilizing effective communication, selecting communication tactics, implementing strategic planning, and evaluating strategic planning.